The effect of one-night sleep deprivation on cognitive functions in healthy young adults - Serkan Pekçetin; Gülnur Öztürk; Buse Çetin; Levent Öztürk (Sleep Science, 2021)
Introduction: The effects of acute sleep deprivation on cognitive function have not been clearly elucidated. The purpose of this study was to evaluate changes in cognitive function in healthy adults after one night of sleep deprivation. Material and Methods: Twenty-one healthy young adults (aged 18-30 years) underwent assessment of cognitive functions before and after one night of total sleep deprivation and an age- and gender-matched control group was assessed before and after a normal night sleep. Cognitive functions were assessed using the Montreal cognitive assessment (MOCA) and trail making test (TMT) parts A and B. Results: General linear model repeated measures demonstrated an insigniﬁcant effect for time × group (sleep deprivation) interaction for MOCA, TMT Part A, and TMT Part B scores after one-night sleep deprivation (p>.05 for all). Conclusion: A single night of sleep deprivation, which can be inevitable in modern society, had no signiﬁcant effect on cognitive performance in healthy adults.